Assessment of a 3D CFD model for GDI spray impact against wall through experiments based on different optical techniques. (September 2016) - Montanaro, Alessandro; Allocca, Luigi; Costa, Michela; Sorge, Ugo
Highlights: A 3D CFD model for GDI sprays dynamics and impact against heated walls is developed. Schlieren and Mie scattering are used to characterize multi- and single-hole sprays for validation purposes. The free spray sub-model is highly portable to different injection conditions. The spray-wall impingement sub-model allows capturing splashing, deposition and secondary evaporation. As expected, turbulent modeling is crucial for the correct prediction of vapor diffusion. Abstract: Performance of internal combustion engines is well known being greatly affected by the air-fuel mixture formation process. In spark ignition engines, in particular, the gasoline direct injection (GDI) technology is currently preferred, as it allows obtaining the desired air-to-fuel ratio distribution at each regime of operation, either by creating stoichiometric mixtures under high power demands, or through charge stratification around the spark plug at intermediate or lower loads. The impact of the gasoline spray on the piston or cylinder walls is a key factor, especially under the so-called wall-guided mixture formation mode. The impact causes droplets rebound and/or the deposition of a liquid film (wallfilm). After being rebounded, droplets undergo what is called secondary atomization. The wallfilm, on the other hand, may remain of no negligible size and evaporate slowly, leading to increased unburned hydrocarbons and particulate matter emissions. Optimization of the heterogeneous mixture behavior in GDI engines is fundamental for guaranteeing high energetic and environmental performance over the whole working map. Computational fluid dynamics (CFD) can be useful in this perspective to effect proper choices of control strategies. Assessment of predictive engine models, able to describe the complex phenomena underlying energy conversion in modern engines, is therefore mandatory to the scope. In the present paper, a basic study is performed on gasoline sprays issuing from high pressure injectors under controlled conditions: the experimental characterization of multi-hole and single-hole GDI sprays in their impact over a plate is carried out with the aim of creating a set of data to be used for the validation of a properly developed simulation model. The multi-hole spray allows accounting for the jet-to-jet interaction and represents a condition closer to the actual gasoline supply mode in present GDI engines. The single-hole injector configuration is instead preferred for a more detailed study, as it allows capturing effects related to the role that diverse parameters characterizing the liquid droplet dynamics play during and after their impingement on heated solid surfaces. The CFD model is conceived with the scope of its future application within numerical calculations of entire engine working cycles. A highly portable free spray sub-model allows correctly reproducing the injection dynamics under different conditions in a confined vessel, while the spray-wall impingement sub-model is shown being able to highlight to an acceptable extent the gasoline splashing and deposition phenomena.